Highly coupled leaky surface acoustic wave on hetero acoustic layer structures based on ScAlN thin films with a c-axis tilt angle. (9th February 2021) - Liu, Huiling; Zhang, Qiaozhen; Zhao, Xiangyong; Wang, Feifei; Chen, Mingzhu; Li, Baichuan; Fu, Sulei; Wang, Weibiao
Abstract: In this paper, we present hetero acoustic layer (HAL) structures based on ScAlN thin films with a c -axis tilt angle. The surface acoustic wave (SAW) excitation modes and their propagation characteristics for different Euler angles (0°, θ, ψ ) of the ScAlN thin film are analyzed using the finite element method. We find that the acoustic field distribution of HAL structures can be adjusted by rotating their Euler angles and that normal SAWs are suppressed; however, leaky SAWs (LSAWs) with significantly improved electromechanical coupling coefficients ( K 2 ) are excited. A maximum K 2 of 14% can be obtained for shear horizontal (SH)-type LSAWs, which is almost 7 times larger than that of the previously reported normal SAW Sezawa mode. Moreover, the optimized HAL structure consisting of (0°, 90°, 60°) ScAlN thin film/SiO2 /AlN/Si simultaneously possesses a larger K 2, a wider bandwidth, and a higher Q value, which is promising for the design and application of wideband SAW devices with high performance.